2022
DOI: 10.3389/fmed.2022.868992
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Maternal Near Miss in Public Hospitals of West Shoa Zone, Central Ethiopia: A Case-Control Study

Abstract: BackgroundMaternal mortality reduction remains a priority to ensure healthy lives and promote wellbeing for mothers and newborns in the new sustainable development goals agenda. There is no evidence-based study done regarding maternal complications and near-miss in the study area.ObjectivesThis study assessed the predictors of maternal near-miss in public hospitals of West Shoa Zone, Central Ethiopia, 2020.MethodsAn unmatched case-control study was conducted among 664 (166 cases and 498 controls) women who gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…From the pooled estimate, there is no association between rural residence and maternal near misses [AOR 0.98, 95% CI, 0.66, 1.30]. Ten studies were included to evaluate the association between ANC and MNM [15,31,36,43,44,[47][48][49][50][51]. From pooled estimates, mothers who have no ANC were 2.18 times more likely to develop MNM when compared to those who have ANC [AOR = 2.18, 95% CI: 1.33, 3.03] (Fig.…”
Section: Factors Associated With Maternal Near Missesmentioning
confidence: 99%
“…From the pooled estimate, there is no association between rural residence and maternal near misses [AOR 0.98, 95% CI, 0.66, 1.30]. Ten studies were included to evaluate the association between ANC and MNM [15,31,36,43,44,[47][48][49][50][51]. From pooled estimates, mothers who have no ANC were 2.18 times more likely to develop MNM when compared to those who have ANC [AOR = 2.18, 95% CI: 1.33, 3.03] (Fig.…”
Section: Factors Associated With Maternal Near Missesmentioning
confidence: 99%
“…[46][47][48] A study showed that walking for more than 1 hour to a health facility was associated with about 4 times higher odds of MNMs. [47] Another study revealed that delays caused by the lack of vehicles increased the odds of MNMs by 8 times. [49] Furthermore, Hadush observed that delays in reaching a health facility contributed to about 40% of the maternal morbidities in their study.…”
Section: Defined By Each Clinical Criterionmentioning
confidence: 99%
“…[45] In many rural areas within sub-Saharan Africa, the paucity of public transportation, high transport costs, and/or poor road infrastructure exacerbate the delays in reaching these facilities during an obstetric complication. [30,37,[46][47] The unavailability of suitable transportation consequently forces some women to walk the distance during an obstetric complication. [46][47][48] A study showed that walking for more than 1 hour to a health facility was associated with about 4 times higher odds of MNMs.…”
Section: Defined By Each Clinical Criterionmentioning
confidence: 99%
See 2 more Smart Citations